Hekate with Apollo and Artemis on a Gem from the Southern Black Sea Region - Manoledakis, Manolis (Istanbuler Mitteilungen, 2024)
This paper discusses the scene on a Roman gem acquired on the south coast of the Black Sea, depicting three figures between two columns. Two of these figures are identified as Apollo and Artemis; for the third, there is no clearly formulated identification, let alone a consensus of opinion. By examining the relation of Hekate with both Artemis and Apollo, the latter particularly in his guise as Agyieus, as is perhaps indicated by the two columns, I endeavour to show that the figure on the right is no other than Hekate. In concluding, I also offer a further interpretation of the scene.